Feminist postcolonial theory: A reader - Lewis, Reina; Mills, Sara (Edinburgh University Press, 2003)
Les lectures ont été choisies pour examiner la nature textuelle et discursive du discours colonial et postcolonial en relation avec le genre et les effets matériels de la condition postcoloniale et des pratiques développées en relation avec celle-ci.
https://search.ebscohost.com/login.aspx?direct=true&scope=site&db=nlebk&db=nlabk&AN=2398481
Keywords: approches et analyses; cours; cycles supérieurs; fem1000; fem7000; féminisme décolonial; genre; histoire et politique; identités LGBTQIA2+; lit3220; premier cycle; ressource en ligne; thématiques

Feminism without borders decolonizing theory, practicing solidarity - Mohanty, Chandra Talpade (Duke University Press, 2003)
"Bringing together classic and new writings of the trailblazing feministtheorist Chandra Talpade Mohanty, Feminism Without Borders addresses someof the most pressing and complex issues facing contemporary feminism. Forgingvital links between daily life and collective action and between theory andpedagogy, Mohanty has been at the vanguard of Third World and internationalfeminist thought and activism for nearly two decades. This collection highlightsthe concerns running throughout her pioneering work: the politics of differenceand solidarity, decolonizing and democratizing feminist practice, the crossingof borders, and the relation of feminist knowledge and scholarship to organizingand social movements. Mohanty offers here a sustained critique of globalizationand urges a reorientation of transnational feminist practice towardsanticapitalist struggles. Her probing and provocative analyses of key conceptsin feminist though - "home", "sisterhood", "community"–Lead the way toward a feminism without borders, afeminism fully engaged with the realities of a transnational world."
Keywords: anticapitalisme; approches et analyses; cours; discours dominant; fem1000; féminisme décolonial; féminisme postcolonial; histoire et politique; premier cycle; privilèges; systèmes d'oppressions; thématiques; transnationalisme